Preparing to intervene in intimate partner violence An interprofessional safety planning and assessment simulation - Childress, Saltanat (Journal of social work education, 2024)
The healthcare system is often the point where intimate partner violence (IPV) can be identified and where intervention strategies are initiated. Healthcare workers often operate in silos; therefore, timely and appropriate intervention depends on effective interdisciplinary communication and teamwork. Interprofessional education initiatives are one method for promoting interdisciplinary cooperation. This article describes an interprofessional educational simulation involving social work and nursing students. One nursing and one social work student were paired to practice screening, referrals, assessments, and safety planning for IPV. The pilot run of this simulation consisted of 140 nursing and 137 social work students. Participants expressed greater confidence in their ability to work with survivors post simulation (t = 5.25, p = .001) and evaluated their knowledge concerning IPV more positively (t = 63.22, p = .001). Focus groups highlighted team synergy as an essential element in the working relationship, the importance of communication skills, and the influence of prior experience on one's approach to domestic violence situations. Future projects should focus on expanding the scope of simulation by addressing more diverse situations as well as by incorporating more professions likely to interact with intimate partner violence survivors